Pete the cat : Pete at the beach - Dean, James; Dean, James, 1957- (New York, NY : Harper, an imprint of Harper/CollinsPublishers, 2013)
Pete the Cat goes to the beach with his mom and brother.
"My first shared reading"--T.p.
Horn Book
School Library Journal
Horn Book, April 2014
School Library Journal, July 2013
0.9
Keywords: Beaches -- Juvenile fiction; Cats -- Juvenile fiction; Beaches -- Fiction; Cats -- Fiction; Beaches -- Fiction; Cats -- Fiction; Readers (Elementary)